2019
DOI: 10.3892/ijo.2019.4919
|View full text |Cite
|
Sign up to set email alerts
|

Clinical importance of long non‑coding RNA LINC00460 expression in EGFR‑mutant lung adenocarcinoma

Abstract: Long non-coding RNAs (lncRNAs) have been reported to be involved in the physiological and pathological processes of tumor pathogenesis, including epithelial-mesenchymal transition (EMT). However, epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitor (TKI) resistance is a major challenge in the treatment of advanced and recurrent EGFR-mutant lung adenocarcinoma. An increased understanding of the underlying mechanisms would aid in the development of effective therapeutic strategies against EGFR-TKI r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 65 publications
(64 reference statements)
1
35
0
Order By: Relevance
“…Several reports show that LINC00460 is a marker for poor OS prognosis across different tumors, such as CESC ( 48 ), HNSC ( 80 ), KIRC ( 81 ), LUAD ( 49 ) and PAAD ( 82 ). In addition, we describe here that LINC00460 high expression is significantly associated with poor survival in three different tumors (GBM, LGG and SARC) but related with a favorable survival rate in BRCA, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports show that LINC00460 is a marker for poor OS prognosis across different tumors, such as CESC ( 48 ), HNSC ( 80 ), KIRC ( 81 ), LUAD ( 49 ) and PAAD ( 82 ). In addition, we describe here that LINC00460 high expression is significantly associated with poor survival in three different tumors (GBM, LGG and SARC) but related with a favorable survival rate in BRCA, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that colorectal cancer patients with high expression of LINC00460 have a higher incidence of tumor metastasis and that this lncRNA is an independent risk factor for prognosis (Zhang et al, 2019). In EGFR-mutant lung cancer, LINC00460 promotes EGFR-TKI resistance, and patients with high LINC00460 expression who receive gefitinib therapy have a lower five-year OS rate than do patients with low LINC00460 expression (Nakano et al, 2020). Lian et al discovered that elevated expression of LINC00460 in osteosarcoma is often accompanied by distant metastasis and poor prognosis, and this lncRNA is expected to become a therapeutic target in osteosarcoma (Lian et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Nakano et al revealed that high expression of LINC00460 led to EGFR‐tyrosine kinase inhibitors resistance in lung cancer cells as a competitive decoy for miR‐149‐5p. The LINC00460 knockout or knockdown in Gefitinib‐resistant NSCLC makes cancer‐resistant cell again sensitive to EGFR‐TKI 71 . Ma et al identified that LINC00460 activates the Gefitinib‐resistance of NSCLC via EGFR by sponging miR‐769‐5p 72 .…”
Section: Crndementioning
confidence: 99%
“…The LINC00460 knockout or knockdown in Gefitinib-resistant NSCLC makes cancer-resistant cell again sensitive to EGFR-TKI. 71 Ma et al identified that LINC00460 activates the Gefitinib-resistance of NSCLC via EGFR by sponging miR-769-5p. 72 Yue et al suggested that overexpression of Linc00460 induced invasion and metastasis via controlling EMT expression level in NSCLC.…”
Section: Linc00460mentioning
confidence: 99%